(untitled) (Research, Society and Development, 2022)
The role of the pharmacist in neonatology is essential for the proper development of the work of the multidisciplinary team, since this is a challenging area in terms of the treatment and prevention of drug-related problems. This professional is able to collaborate in the identification of risks related to the therapy and intervene with the prescriber. Thus, the present study aimed to validate an instrument for evaluating pharmacotherapeutic risk factors according to the profile of patients hospitalized in a Neonatal Unit to address the need for pharmaceutical follow-up. For this, a quantitative, qualitative, descriptive and retrospective study was carried out. The sample consisted of data from the score applied weekly in the clinical pharmacy service of the Neonatal ICU’s during April to June 2021. With the score it was possible to categorize patients into "HIGH RISK", "MEDIUM RISK" and "LOW RISK" and relate with their clinical conditions. Data were collected from 191 patients, of which 45% corresponded to the "LOW RISK" category, 50.3% to the "MODERATE RISK" category and 4.7% to the "HIGH RISK" category. Data related to the number of intravenous drugs, vasoactive drugs, psychotropic drugs, restricted use antimicrobials, use of pulmonary surfactant, drugs administered enterally through tubes, use of parenteral nutrition and wards analyzed according to the clinical outcome were statistically significant. Thus, the present study was able to show that the insertion of tools to improve the clinical outcome in neonatology is extremely important, as well as an excellent instrument for the pharmacist.